Sulfur types distribution and the fast thermal-cracking behaviors of sulfur-containing compounds in Buton oil sand bitumen. (15th February 2022) - Hao, Junhui; Gong, Zheng; Yang, Zhanxu; Tian, Yuanyu; Wang, Chengbiao
Highlights: Types of SCCs in Buton OSB were quantified at the level of group-fractions. Sulfidic sulfur and thiophenic sulfur had the highest enrichment in the aromatics. SCCs in oil sand oil produced from the fast pyrolysis of OSB were evaluated. The composition of SCCs in oil sand oil tended to be enriched with temperature. SCCs in oil sand oil obtained over calcium aluminate had the most abundant classes. Abstract: The distribution of various types of sulfur in Buton oil sand bitumen (OSB) were investigated at the level of group-fractions corresponding to saturates, aromatics, resins and asphaltens (SARA). The separation of different types of sulfur-containing compounds (SCCs) in saturates and aromatics with weak polarity was performed using selective oxidization coupled with alumina column chromatography. However, various types of SCCs were isolated from resins via selective oxidization combined with solvent fractional extraction. It was found that sulfide sulfur, thiophenic sulfur and sulfoxide/sulfone sulfur accounted for 39.31%, 53.93% and 6.74% in total sulfur of OSB, respectively. Sulfidic sulfur and thiophenic sulfur in OSB had the highest enrichment in aromatics, followed by that in asphaltenes and resins. In order to further link the theoretical study with the actual process of thermal cracking process, the fast thermal cracking of OSB to produce oil sand oil under different temperature and over silica sand, calcium aluminate and FCC catalyst was conducted by a laboratory-scale fluidized bed reactor. The composition and classes of SCCs existed in oil sand oil were evaluated via GC–MS, which were indispensable to gain an in-depth insight into thermal cracking behavior of SCCs in OSB. Results indicated that SCCs in oil sand oil obtained under different temperature and over different heat carriers had the distinct composition, and yet were all classified into up to 11 classes. The detected SCCs in oil sand oil obtained over silica sand at different temperatures all contained AT&AM, thiophenes, BTs, HydroDBTs, DBTs, HydroNTs, and NTs. The composition and classes of SCCs in oil sand oil, nonetheless, were inclined to be enriched as the temperature enhanced. Furthermore, the detected SCCs in oil sand oil obtained over calcium aluminate featured the most abundant class distribution, followed by that over silica sand and FCC catalyst. The relative content of AT&AM, thiophenes and BTs, the relative content of NTs and four species of Hydrothiophenes, and the relative content of DBTs, PTs and BNTs accounting for SCCs in oil sand oil was largest when the heat carriers were silica sand, calcium aluminate and FCC catalyst, respectively.